Rainfall Anomaly Analysis and Seasonal Climate Projection in Palembang City Using CHIRPS Data and Z-Score Method - Shofwan Mahsyurdin; Ermatita Ermatita (Sultan Publisher, 2026)
Using CHIRPS daily rainfall data (1981–2024) which is the standard climatological period according to the World Meteorological Organization (WMO) which is at least 30 years, rainfall anomalies during the dry season (May–October) are analyzed using the Z-score statistical approach. The 2025 prediction scenario integrates moderate El Niño (SST +1.0) and negative IOD (–0.5) as correction factors for the climatological average. Anomalous rainfall values ​​will be converted into z-score values ​​if Z>0 then the value is above the average (wet/hot) and vice versa if Z<0 the value is below the average (dry/cold). The results of the study indicate a significant potential for negative anomalies (Z-score < 0) in most areas of Palembang, indicating a decrease in rainfall below normal levels, with the peak of the dry season projected in August–September 2025. For the rainfall anomaly value, it has been converted into a z-score value that has been explained using the formula so that the significant climate trend in 2024 is 0.34 according to the Standardized Rainfall Index (SPI) in the normal or mild condition category. Finally, the rainfall prediction graph for 2025 shows the final results of the analysis process, namely the highest rainfall of 369.173 mm in April and the lowest rainfall of 60.12 mm in August.